Influence of ethanolic extract of pineapple (Ananas comosus) peel on the inhibition of enzymatic browning and preservation of organoleptic properties of canchan potato (Solanum tuberosum L.) (Agroindustrial Science, 2025)
Chemical-synthetic methods have been developed to preserve the organoleptic properties of potatoes, but their consumption may be harmful to health. Therefore, this research aims to evaluate the preservation capacity of ethanolic extract from the peel of Golden variety pineapple at different concentrations (3%, 7%, 10%, and 15%), compared to solutions of 0.1% sodium metabisulfite, 0.1% citric acid, 0.1% ascorbic acid, and a control sample of untreated potatoes. The study assesses the organoleptic characteristics and the effect of these treatments on enzymatic browning in Canchan variety potatoes over 14 days of observation. The CIElab* color parameters and ∆E were measured at 0, 3, 7, 10, and 14 days, respectively. Additionally, a sensory analysis was conducted, in which nine trained panelists determined the sensory profiles (quality and defects) and the acceptability of each treatment. The results showed that the extracts had a positive effect on color preservation, with the 10% and 15% extracts yielding the best results; however, these treatments exhibited low preservation of the characteristic potato flavor.
Keywords: ethanolic extract; enzymatic browning; pineapple peel; natural extract; sensorial analysis